Genetic parameter estimates for the weight and fleece traits in Chokla sheep - Kumar, Ravindra; Singh, C V; Mehta, B S (The Indian Journal of Animal Sciences, 2005)
Genetic parameters were estimated for weights of lambs at birth, weaning and 6 months and fleece yield using leastsquares and univariate and multivariate animal models with REML procedure. The data considered from 1214 animals descendent from 110 sires, 422 dams, 36 paternal grandsires, 44 paternal grand mothers, 69 maternal grand sires and 131 maternal grand mother of Chokla sheep maintained at Central Sheep and Wool Research Institute, Avikanagr. Traits analyzed were birth weight (BWT), weaning weight (WWT), 6 months weight (6 WT) and first greasy fleece yield (GFY1 ). Variance components were estimated using least-squares analysis and restricted maximum likelihood computer ptogramme with an animal model including fixed effect for sex and year of birth and random effect for sire. Additive (direct), environmental and phenotypic variances estimated from univariate and multivariate animal models agreed closely for all the traits. Similarly, variance estimated from model 2 and model 8 analysis agreed for all the traits. Model 2 had slightly higher additive variance for weaning, 6 months and greasy fleece yield but lower for birth weight than model 8. For growth traits. REML analysis had lowest additive variance while model 2 had higher. Multivariate REML had estimated higher additive and enviromental covariance than model 2, among growth traits. Model 2 also had higher environmental covariance among first fleece yield and growth trails than multivariate REML analysis. The H² estimates for birth weight were 0.138,0.147.0.306 and 0.307, respectively, under model 2, model 8. univariate and multivariate analysis. The h² estimates for weaning weight were 0.238 , 0.185,0.204 and 0.216, respectively, under model 2, model 18 , univariate and multivariate analysis. The h² estimates for 6 month weight and first greasy fleece yield mvdrl 2, model 8, univariate and multivariate analysis were 0.245. 0.161, 0.240 and 0.226 and 0.242, 0.144, 0.103 and 0.097 respectively. Genetic correlations ranged from 0.391 (between birth and 6 month weight) to 0.822 (between weaning and first greasy fleece yield) in model 2 of LSA. whereas in multivariate REML it ranged from 0.245 (between 6 months and first greasy Hecce yield) to 0.909 (between weaning and 6 months weight). Multivariate REML analysis had explained more variation in genetic correlations than LSA. The phenotypic correlations ranged from 0.233 (between birth weight and first greasy fleece yield) to 0.722 (between birth weight and first greasy yield) under model 2 of LSA and from 0.220 (between birth weight and first greasy fleece weight) to 0.725 (between weaning weight and 6 month weight) under multivariate analysis. The environmental correlations ranged from 0.117 (between BWT and FGY 1) to 0.695 (between WWT and FGY 1). These estimates of genetic parameters between growth and fleece yield traits can be used to construct multiple trait selection indexes for genetic improvement of Avikalin strain of sheep.